Progressive nigrostriatal terminal dysfunction and degeneration in the engrailed1 heterozygous mouse model of Parkinson's disease - Ulrika Nordström; Geneviève Beauvais; Anamitra Ghosh; Baby Chakrapani Pulikkaparambil Sasidharan; Martin Lundblad; Julia Fuchs; Rajiv L. Joshi; Jack W. Lipton; Andrew Roholt; Satish Medicetty; Timothy N. Feinstein; Jennifer A. Steiner; et al. (Neurobiology of Disease, 2015)
Current research on Parkinson's disease (PD) pathogenesis requires relevant animal models that mimic the gradual and progressive development of neuronal dysfunction and degeneration that characterizes the disease. Polymorphisms in engrailed 1 (En1), a homeobox transcription factor that is crucial for both the development and survival of mesencephalic dopaminergic neurons, are associated with sporadic PD. This suggests that En1 mutant mice might be a promising candidate PD model. Indeed, a mouse that lacks one En1 allele exhibits decreased mitochondrial complex I activity and progressive midbrain dopamine neuron degeneration in adulthood, both features associated with PD. We aimed to further characterize the disease-like phenotype of these En1+/− mice with a focus on early neurodegenerative changes that can be utilized to score efficacy of future disease modifying studies. We observed early terminal defects in the dopaminergic nigrostriatal pathway in En1+/− mice. Several weeks before a significant loss of dopaminergic neurons in the substantia nigra could be detected, we found that striatal terminals expressing high levels of dopaminergic neuron markers TH, VMAT2, and DAT were dystrophic and swollen. Using transmission electron microscopy, we identified electron dense bodies consistent with abnormal autophagic vacuoles in these terminal swellings. In line with these findings, we detected an up-regulation of the mTOR pathway, concurrent with a downregulation of the autophagic marker LC3B, in ventral midbrain and nigral dopaminergic neurons of the En1+/− mice. This supports the notion that autophagic protein degradation is reduced in the absence of one En1 allele. We imaged the nigrostriatal pathway using the CLARITY technique and observed many fragmented axons in the medial forebrain bundle of the En1+/− mice, consistent with axonal maintenance failure. Using in vivo electrochemistry, we found that nigrostriatal terminals in the dorsal striatum were severely deficient in dopamine release and reuptake. Our findings support a progressive retrograde degeneration of En1+/− nigrostriatal neurons, akin to what is suggested to occur in PD. We suggest that using the En1+/− mice as a model will provide further key insights into PD pathogenesis, and propose that axon terminal integrity and function can be utilized to estimate dopaminergic neuron health and efficacy of experimental PD therapies.